Mixed Ionic and Electronic Conducting Eutectogels for 3D-Printable Wearable Sensors and Bioelectrodes - Picchio, Matías Luis (2022)
Eutectogels are a new class of soft ion conductive materials that are attracting attention as an alternative to conventional hydrogels and costly ionic liquid gels to build wearable sensors and bioelectrodes. Herein, the first example of mixed ionic and electronic conductive eutectogels showing high adhesion, flexibility, nonvolatility, and reversible low-temperature gel transition for 3D printing manufacturing is reporting. The eutectogels consist of choline chloride/glycerol deep eutectic solvent, poly(3,4-ethylenedioxythiophene): lignin sulfonate, and gelatin as the biocompatible polymer matrix. These soft materials are flexible and stretchable, show high ionic and electronic conductivities of 7.3 and 8.7 mS cm−1, respectively, and have high adhesion energy. Due to this unique combination of properties, they could be applied as strain sensors to precisely detect physical movements. Furthermore, these soft mixed ionic electronic conductors possess excellent capacity as conformal electrodes to record epidermal physiological signals, such as electrocardiograms and electromyograms, over a long time.